Potensi Antibakteri Kombinan Zingiber officinale Roscoe. Var. Rubrum dengan Cinnamomum burmannii terhadap Staphylococcus aureus - Ruth Mayana Rumanti; Suprianto Suprianto; Jakub Tarigan; Arinri Misnangin Sritala Ramadani (LPPM STIKes Indah Medan, 2021)
Red Ginger (Zingiber officinale Roscoe. Var. Rubrum) and Cinnamon (Cinnamomum burmannii) contain alkaloids, flavonoids, saponins, tannins, triterpenoids and essential oils. which is antibacterial that causes pharyngitis by Staphylococcus aureus. This study aims to determine the antibacterial potency of the combination of Red Ginger (Zingiber officinale Roscoe. Var. Rubrum) and Cinnamon (Cinnamomum burmannii) extract against Staphylococcus aureus. Experimental research includes the extraction of the compound components in red ginger and cinnamon by maceration with 70% ethanol. Inhibition was tested by diffusion method. Combination of concentration of Red Ginger and Cinnamon extracts of 5% : 40%; 10%: 30%; 20%: 20%; 30%: 10% and 40%: 5%. The combination of red ginger and cinnamon extract has antibacterial activity against pharyngitis-causing bacteria, namely Staphylococcus aureus with a strong response at a concentration of 5%: 40%.